Changes in hydrogen production and polymer accumulation upon sulfur-deprivation in purple photosynthetic bacteria - Melnicki, M.; Eroglu, Ela; Melis, A. (Elsevier Ltd, 2009)
The work investigated physiological conditions directing cellular metabolism toward either H2-production or storage polymer accumulation in purple photosynthetic bacteria. Hydrogen-producing cultures of the purple anoxygenic photosynthetic bacterium Rhodospirillum rubrum were resuspended in media lacking sulfur (S) nutrients. S-deprived cultures displayed lack of growth, cessation of bacteriochlorophyll and protein accumulation, and inhibition of H2 evolution. Cell volume increased substantially and large amounts of polymer were found to accumulate extracellularly. Poly-ß-hydroxybutyrate (PHB) content increased about 3.5-fold within 24 h of S-deprivation. Most cells remained viable after 100 h of S-deprivation and cultures were capable of resuming growth and H2-production when supplemented with sulfate. Transcript levels, protein amount, and activity of the nitrogenase enzyme, which are responsible for H2-production, decreased with a halftime of about 15 h upon S-deprivation. In addition, the nitrogenase NifH subunits were modified by ADP-ribosylation, indicating post-translational inactivation. Comparative aconitase activity measurements of control and S-deprived cells failed to indicate a general stress to Fe-S proteins, as aconitase, a Fe-S protein in the citric acid cycle sensitive to oxidative stress, maintained activity throughout the course of the S-deprivation. In contrast to nifH transcriptional down-regulation, expression of cysK (encoding cysteine synthase) was upregulated in response to S-deprivation. The described physiology is not specific to R. rubrum, as Rhodobacter sphaeroides and Rhodopseudomonas palustris exhibited a similar response to S-deprivation. It is suggested that manipulation of the supply of S-nutrients may serve as a tool for the alternative production of H2 or PHB in purple photosynthetic bacteria, thus affording opportunities to design photobiological systems that serve in both energy conversion and storage processes. © 2009 International Association for Hydrogen Energy.